ANALISIS PENGARUH LOAN TO DEPOSIT RATIO DAN BEBAN OPERASIONAL PENDAPATAN OPERASIONAL TERHADAP PROFITABILITAS BANK PEMBANGUNAN DAERAH PULAU KALIMANTAN - Dewi Karimah; Ida Nuraini (Program Studi Ekonomi Pembangunan, 2018)
The objectives of this research is to analyze the effect of variable Loan To Deposit Ratio (LDR), and Cost of Operations to Income Operations (BOPO) on profitability (ROA) of Regional Development Banks in Kalimantan Island. This research using data from the publication of the annual financial statements from each Regional Development Banks in Kalimantan Island. The number of samples as much as 4 Regional Development Banks with the period in 2008-2017. Analitycal techniques used was multiple linear analysis. The result showed the simultaneously (Test F) all free variables affect the dependent variable with a significant value of 0,000. While partially (T test), variable X1 (LDR) has a positive and significant influence on the dependent variable Y (ROA). While X2 (BOPO) has a negative and significant influence on the dependent variable Y (ROA). Determination coefficient (R2) from the regression result of 0,676 this shows the ability of independent variables in explaining the dependent variable changes of 67,6% while the remaining 32,4% is explained by other variable outside the study.Keyword : LDR, BOPO, and Profitability (ROA).